IMPLEMENTATION OF AKHLAKUL KARIMAH THROUGH THE HABITUATION OF BOSO KROMO IN COMMUNICATING AMONG SANTRI DARUN NAJAH ISLAMIC BOARDING SCHOOL - Ilmi, Yuʻfiyah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Efforts to form human beings with good morals are the goal of education in general, especially Islamic boarding schools. Implementation of akhlakul karimah through the habit of Boso Kromo in communicating well among students, will be able to help the students themselves in communicating with others and can make the good name of the alma mater they bear. Meanwhile, at the Darun Najah Islamic Boarding School, Petahunan Village, Sumbersuko District, Lumajang Regency has implemented procedures for having good morals through the habit of boso kramo in communicating, both to caregivers, teachers and friends and even family. This can be attempted through direct examples from caregivers and teachers who are exemplary figures in the pesantren. But in reality there are still some students who have difficulty communicating using Boso Kromo because of the limited vocabulary of Boso Kromo words that are known by students. The purpose of this study was to find out how to implement Akhlakul Karimah through the habituation of Boso Kromo in communicating among Santri. In order to collect data, the authors use observation techniques, interviews and data analysis.